Krzysztof Kieślowski’s “Decalogue” as a Quality TV Series - Talarczyk, Monika (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The text is dedicated to The Decalogue (Dekalog,1988) by Krzysztof Kieslowski and analyses the television series through the prism of genre and contemporary television studies, including the concept of quality television. Kieslowski’s series fulfills all the criteria assigned to the contemporary new generation television series, and can act as a reference point for interpreting Poland’s first new generation series by HBO, In treatment (Bez tajemnic, 2011–2013). The two titles are also linked by the same Polish film tradition, i.e. the cinema of moral concern, even though In treatment is based on foreign format.